Best practices in trade policy reform - Thomas, Vinod (O.U.P. for the World Bank OxfordGB, 1991)
Examines how much trade liberalization has actually taken place and how effective it has been in promoting economic growth. Highlights practical problems and constraints, both economic and political. Draws on the experience of developing countries with trade policy design and implementation to suggest how they can obtain stronger and more sustainable results. Finds that where reforms have been significant and credible, economic growth and the balance of payments have improved.